2011
DOI: 10.3892/or.2011.1374
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of SALL4 in lung cancer and its importance in cell proliferation

Abstract: Abstract. Few target molecules have been identified that enable the diagnosis of lung cancer with high sensitivity and specificity, especially in the early clinical stages. Herein, we present the first evidence for mRNA overexpression of SALL4, a transcription factor essential for embryonic development and the self-renewal of embryonic stem cells, in lung cancer. Analysis using cancerous and noncancerous tissues revealed that the sensitivity and specificity of SALL4 mRNA were 85.1 and 92.9%, respectively, esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 24 publications
(32 reference statements)
2
47
0
Order By: Relevance
“…(28, 29) As a marker for stem cells, SALL4 expression is proposed to represent a stem cell phenotype in HCC, as shown in other cancer types. (3135) These studies indicate that stem cell features, defined by nuclear SALL4 immunohistochemistry and/or mRNA expression, correlate with an aggressive course and poor prognosis. Importantly, in both HCC studies, SALL4 immunoreactivity was seen in 55.6% (n=171) and 85% (n=20) of cases, respectively, and overexpression by microarray analysis was detected in 50% of cases.…”
Section: Discussionmentioning
confidence: 95%
“…(28, 29) As a marker for stem cells, SALL4 expression is proposed to represent a stem cell phenotype in HCC, as shown in other cancer types. (3135) These studies indicate that stem cell features, defined by nuclear SALL4 immunohistochemistry and/or mRNA expression, correlate with an aggressive course and poor prognosis. Importantly, in both HCC studies, SALL4 immunoreactivity was seen in 55.6% (n=171) and 85% (n=20) of cases, respectively, and overexpression by microarray analysis was detected in 50% of cases.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, SALL4 promoted the proliferation, invasion, migration, EMT, chemoresistance, and the maintenance of cancer stem cells in different cancer types, and targeted inhibition of SALL4 has shown efficient therapeutic effects on cancer [22, 28, 3840]. For instance, knockdown of SALL4 causes inhibition of lung cancer cell proliferation, induced by cell cycle arrest at the G1/early S phase [41]. In the present study, we found that restoration of SALL4 reversed the suppressive effect of miR-98 on the proliferation, migration, invasion and EMT of HCC cells, suggesting that miR-98 plays a suppressive role in HCC via inhibition of SALL4.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of its expression and epigenetic status have shown that SALL4 is de-regulated and aberrantly expressed in various cancers (Review in 64 ) such as leukemia 65 , germ cell tumors 6667 , hepatocellular carcinoma (HCC) 2468 , gastric cancer 20,6973 , colorectal carcinoma 7476 , esophageal squamous cell carcinoma 77,78 , breast cancer 7981 , endometrial cancer 82,83 , lung cancer 8486 and glioma 87 . Functionally, SALL4 is important for the survival 38,80,82,8893 , drug resistance 82,94 and metastasis 69,82 of many of these cancer cells (Figure 4).…”
Section: Sall4 In Cancersmentioning
confidence: 99%